How to Teach the Test of Arabic as a Foreign Language (TOAFL) Case Study in the Preparatory/Special Class of Islamic Secondary School | طريقة تعليم اختبار اللغة العربية كاللّغة للناطقين بغيرها الأجنبية (TOAFL) - Hermanto, Ayub; Hafidz, Muhammad; Fuadi, Abdul Hafizh Nur (NAJAH BESTARI, 2023)
This study discusses the TOAFL learning method in the preparation class. The research was conducted on the preparatory class program at MBI Amanatul Ummah Mojokerto which is designed as a learning support facility for students who are willing and have interests and talents to continue their studies in Middle Eastern countries.This research uses a descriptive qualitative research with a case study approach in the MBI Amanatul Ummah Mojokerto preparatory class.The results showed that TOAFL learning in the MBI Amanatul Ummah Mojokerto preparation class was as follows: first, TOAFL learning used several methods, namely, grammatical and tarjamah methods, direct methods, audio-lingual methods, theoretical practice methods, reading methods, and mixed methods. second, the material used in TOAFL learning, namely, al-lughoh al-'arobiyah al-mu'ashiroh, in which there are 2 volumes with 1 volume containing 12 materials or themes.